2002
DOI: 10.5713/ajas.2002.1496
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Zinc Effects on Growth Performance and Immune Response of Endotoxemic Growing Pigs

Abstract: A 2×3 factorial arrangement of treatments was used in a completely randomized design to determine the effects of dietary Zn on performance and immune response of acutely endotoxemic growing pigs (n=96, mean BW=24.9 kg). Factors included 1) intramuscular injection of 10 µg/kg BW of Escherichia coli lipopolysaccharide (LPS) or control and 2) supplemental Zn at 10, 50, or 150 ppm. Diets were fed beginning after weaning (initial body weight=7.6 kg) in the nursery and continued for 16 d into the grower phase. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Interestingly, pigs receiving ZnAA tended to have a slightly elevated Tr (+0.27°C) compared with ZnC-fed pigs and this agrees with zinc's effects in an endotoxemia model (Roberts et al, 2002). This is surprising, as ZnAA-supplemented pigs had similar FI and BW, which are two key variables associated with basal heat production.…”
Section: Discussionmentioning
confidence: 54%
“…Interestingly, pigs receiving ZnAA tended to have a slightly elevated Tr (+0.27°C) compared with ZnC-fed pigs and this agrees with zinc's effects in an endotoxemia model (Roberts et al, 2002). This is surprising, as ZnAA-supplemented pigs had similar FI and BW, which are two key variables associated with basal heat production.…”
Section: Discussionmentioning
confidence: 54%
“…A lower serum Zn level (13.190.4 mg/ 100 ml) was recorded in pig, following supplementation of 12 ppm of Zn in diet, whereas, a higher serum Zn level (61.190.1.9 mg/100 ml) was observed, following supplementation of 90 ppm of Zn (Prasad et al 1969). Similarly, Roberts et al (2002) observed higher serum Zn (1.3790.10 ppm), following supplementation of 150 ppm Zn as compared to 0.9890.8 and 1.0890.08 ppm, following supplementation of 10 and 50 ppm Zn in grower pigs, respectively. Serum Zn of 227 mg/dl was reported in gilts following supplementation of 5000 ppm of Zn through diet as compared to 83, 59 and 58 mg/dl, following supplementation of 500, 50 and 0 ppm Zn, respectively (Hill et al 1983).…”
Section: Resultsmentioning
confidence: 91%
“…Interestingly, relative to LPS-CON cows, feeding complexed Zn reduced the febrile response to LPS. Both an increased (Roberts et al, 2002;Sanz Fernandez et al, 2014) and decreased (Chirase et al, 1991;Pearce et al, 2015;Abuajamieh et al, 2016) Tr response has been observed with complexed Zn following immunoactivation, and the variability is presumably cytokine driven. Circulating cytokines (e.g., tumor necrosis factor-α or IL-1β) have pyrogenic properties and are altered by Zn in pigs (Klosterhalfen et al, 1996;Paulk et al, 2014;Mayorga et al, 2018), humans (Bao et al, 2010), chickens (Jarosz et al, 2017a), and cattle (Batistel et al, 2016).…”
Section: Discussionmentioning
confidence: 99%